Enhanced visibility of colonic neoplasms using formulaic ratio imaging of native fluorescence. Issue 9 (30th September 2013) - Banerjee, Bhaskar; Rial, Nathaniel S.; Renkoski, Timothy; Graves, Logan R.; Reid, Sirandon A.H.; Hu, Chengcheng; Tsikitis, Vassiliki L.; Nfonsom, Valentine; Pugh, Judith; Utzinger, Urs
Abstract Background and Objectives Colonoscopy is the preferred method for colon cancer screening, but can miss polyps and flat neoplasms with low color contrast. The objective was to develop a new autofluorescence method that improves image contrast of colonic neoplasms. Study Design/Materials and Methods We selected the three strongest native fluorescence signals and developed a novel method where fluorescence images are processed in a ratiometric formula to represent the likely cellular and structural changes associated with neoplasia. Native fluorescence images of fresh surgical specimens of the colon containing normal mucosa, polypoid and flat adenomas as well as adenocarcinoma were recorded using a prototype multi‐spectral imager. Sixteen patients, with a mean age of 62 years (range 28–81) undergoing elective resection for colonic neoplasms were enrolled. High contrast images were seen with fluorescence from tryptophan (Tryp), flavin adenine dinucleotide (FAD) and collagen. Results When the image intensity of Tryp was divided pixel by pixel, by the intensities of FAD and collagen, the resulting formulaic ratio (FR) images were of exceptionally high contrast. The FR images of adenomas and adenocarcinomas had increased Weber contrast. Conclusions FR imaging is a novel imaging process that represents the likely metabolic and structural changes in colonic neoplasia that produces images with remarkably high contrast. Lasers Surg. Med. 45:573–581, 2013. © 2013 Wiley Periodicals, Inc.